ANALYSIS OF FAITH MESSAGES IN THE JARAN KENCAK ART TRADITION - Farid Ali Yafi (Journal Analytica Islamica, 2024)
Jaran Kenchak, Faith, Tradition, Sumenep, Preaching, Tauhid This study examines the faith messages in the Jaran Kenchak tradition in Cabbiya Village, Talango District, Sumenep Regency, Madura. This study aims to identify and analyze the faith messages contained in the Jaran Kenchak tradition in Cabbiya Village, as well as how the local community interprets and preserves this tradition in their religious context. Using descriptive qualitative research methods and ethnographic approaches, data collection was carried out through field observations, in-depth interviews with community leaders, cultural observers, and activists of the Jaran Kenchak tradition in Sumenep, and documentation. This study also analyzes the forms, symbols, and processions in Jaran Kenchak related to the teachings of tauhid and Islamic values. The results of the study indicate that Jaran Kenchak is not only a symbol of cultural pride, but also a means of preaching that strengthens Islamic faith among the people of Sumenep.